Comparative Effects of Human Neural Stem Cells and Oligodendrocyte Progenitor Cells on the Neurobehavioral Disorders of Experimental Autoimmune Encephalomyelitis Mice. (26th June 2016) - Bae, Dae-Kwon; Park, Dongsun; Lee, Sun Hee; Yang, Goeun; Kyung, Jangbeen; Kim, Dajeong; Shin, Kyungha; Choi, Ehn-Kyoung; Kim, Gonhyung; Hong, Jin Tae; Kim, Seung U.; Kim, Yun-Bae
Abstract : Since multiple sclerosis (MS) is featured with widespread demyelination caused by autoimmune response, we investigated the recovery effects of F3.olig2 progenitors, established by transducing human neural stem cells (F3 NSCs) with Olig2 transcription factor, in myelin oligodendrocyte glycoprotein- (MOG-) induced experimental autoimmune encephalomyelitis (EAE) model mice. Six days after EAE induction, F3 or F3.olig2 cells (1 × 10 6 /mouse) were intravenously transplanted. MOG-injected mice displayed severe neurobehavioral deficits which were remarkably attenuated and restored by cell transplantation, in which F3.olig2 cells were superior to its parental F3 cells. Transplanted cells migrated to the injured spinal cord, matured to oligodendrocytes, and produced myelin basic proteins (MBP). The F3.olig2 cells expressed growth and neurotrophic factors including brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), ciliary neurotrophic factor (CNTF), and leukemia inhibitory factor (LIF). In addition, the transplanted cells markedly attenuated inflammatory cell infiltration, reduced cytokine levels in the spinal cord and lymph nodes, and protected host myelins. The results indicate that F3.olig2 cells restore neurobehavioral symptoms of EAE mice by regulating autoimmune inflammatory responses as well as by stimulating remyelination and that F3.olig2 progenitors could be a candidate for the cell therapy of demyelinating diseases including MS.